Arthroscopic bone grafting for Schatzker III tibial plateau fractures: a retrospective comparative study - Rongfang Zhang; Yuqi Wang; HongBo Liu; Yuanxin Qiao; Xi Zhang (Scientific Reports)
Abstract This study aims to compare the clinical efficacy of arthroscopically assisted treatment versus traditional open reduction for Schatzker type III posterolateral tibial plateau collapse fractures. We retrospectively analyzed clinical data from 40 patients with Schatzker type III fractures (lateral plateau collapse) treated at our hospital between October 2020 and March 2024. Patients were divided into two groups: the arthroscopy group (n = 19) and the open incision group (n = 21). General patient information, hospitalization costs, length of stay, and wound length were collected. All patients were followed for one year postoperatively, with knee function assessed using the Lysholm score. Categorical data were analyzed using the chi-square test, and continuous variables using independent sample t-tests. A p-value < 0.05 was considered statistically significant. There were no significant differences in baseline characteristics between the two groups. The arthroscopy group had significantly shorter operation times and postoperative hospital stays compared to the open incision group (p < 0.05). Additionally, surgical costs were significantly lower in the arthroscopy group (p < 0.05). At 3 months postoperatively, the arthroscopy group demonstrated significantly higher Lysholm scores compared to the open incision group. However, there was no significant difference in Lysholm scores between the two groups at the 6 months and 1-year follow-up (p > 0.05). Compared to traditional open reduction and internal fixation, arthroscopic treatment of Schatzker type III posterolateral tibial plateau collapse fractures offers several advantages, including shorter operative time, lower cost, fewer incision-related complications, no need for secondary removal of internal fixation, faster postoperative functional recovery, and minimally invasive, cosmetically favorable incisions.